Self expanding metal stents for palliation of dysphagia due to esophageal malignancies - , Ahmet DOBRUCALI, Mustafa ÖZGÜROĞLU, Gökhan DEMİR and , Tayfun KARAHASANOĞLU and , Hülya UZUNİSMAİL and , Hayrettin CEBECİ and; gun OKTAY and; mail DİNÇ (Turkish Journal of Gastroenterology 1, 2019)
-